Primary metabolism and initial development of grafted black pepper seedlings (Research, Society and Development, 2021)
The production of black pepper seedlings through grafting is a promising strategy to mitigate the effect of environmental stresses, such as drought, that limit its cultivation. However, studies on compatibility between grafts and rootstocks are still scarce, especially considering the wild species of the genus Piper and the cultivated genotypes of black pepper. The objective of this work was to evaluate the relationship between primary metabolism and the development of black pepper seedlings obtained through intra- and interspecific grafting. The method used was that of cleft lateral grafting, as graft the Bragantina cultivar, better known in the world as ‘Panniyur 1’, and ‘Kottanadan’ cultivar and three wild species (Piper hispidum, Piper aduncum and Piper tuberculatum) were used as root-stock. As a control, ´Bragantina` was grafted onto itself (homograft). The experiment was carried out for 110 days and the seedlings were evaluated for development, gas exchange, and carbohydrate allocation. The rootstock influences the development and primary metabolism of seedlings. P. aduncum showed greater initial compatibility among wild species, due to less impediment to carbohydrate flow. P. tuberculatum showed early incompatibility, as the grafts died. The seedlings grafted on P. hispidum and 'Kottanadan' had initial compatibility with an average of 78% survival and 60% budding, but they may have late incompatibility due to limitation of carbohydrate flow.